Counter‑Narratives through the lens of al‑Baraddūnī: The case of the 1962 Yemeni revolution - Noura Kamal (Arabian Humanities)
One of the main features of Yemeni historiography is that for many centuries it focused on the history of rulers and the biographies of elite scholars. Since the revolution and the end of the Yemeni Imamate in 1962, scholars such as ʻAbd Allāh al‑Baraddūnī began to focus on popular narratives that retold history from the vantage point of those who, historically, have been marginalized by Yemen’s ruling elites. Al‑Baraddūnī’s endeavours to rehabilitate popular narratives and historiography were a prominent reaction to the dominant formal history, literature and art during the Imamate, and were triggered by the spirit of the 1962 revolution in Yemen’s north. This paper explores how al‑Baraddūnī worked towards the rehabilitation of the roles of formerly marginalized people in Yemen, and how folk history provided hitherto undocumented and “unofficial” knowledge about the changing social, political and power relations in twentieth‑century Yemen.